2002
DOI: 10.1007/0-306-46817-4_25
|View full text |Cite
|
Sign up to set email alerts
|

Design and Testing of Ribozymes for Cancer Gene Therapy

Abstract: This chapter describes procedural aspects for development of ribozymes in general, and specifically, that cleave mRNA to an essential cellular gene, the AC40 subunit of RNA pol I. Ribozyme design includes functional selection of binding sites followed by computer modeling. These ribozymes are being used in vectors that target expression to the prostate via tissue specific promoters (Voeks, Norris, and Clawson, 1998) and have demonstrated efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Using our CLIP [Benedict et al, 1998;Crone et al, 1999;Ren et al, 1999;Norris et al, 2000], SNIP and SNIP AA Rz expression cassettes [Zhang et al, 2002;Pan et al, 2003, hRz targeted to library selected sites were shown to effectively block hepatitis B virus (HBV) replication within cultured HepG2 cells [Pan et al, 2001], with major decreases in HBSAg secretion, viral mRNAs, and viral DNA. We also documented efficient downregulation of human papillomavirus (HPV) type 16 and 11 E6/E7 transcripts within cultured cells [Pan et al, 2003.…”
Section: In Vitro Library Selectionmentioning
confidence: 98%
“…Using our CLIP [Benedict et al, 1998;Crone et al, 1999;Ren et al, 1999;Norris et al, 2000], SNIP and SNIP AA Rz expression cassettes [Zhang et al, 2002;Pan et al, 2003, hRz targeted to library selected sites were shown to effectively block hepatitis B virus (HBV) replication within cultured HepG2 cells [Pan et al, 2001], with major decreases in HBSAg secretion, viral mRNAs, and viral DNA. We also documented efficient downregulation of human papillomavirus (HPV) type 16 and 11 E6/E7 transcripts within cultured cells [Pan et al, 2003.…”
Section: In Vitro Library Selectionmentioning
confidence: 98%
“…A ribozyme is a specifically structured RNA molecule with catalyzing activity (Figure 3(a)). It has been used as a potential therapy for treating cancers and infectious diseases by targeting and cleaving specific cancer or viral gene transcripts 55,56. As circular permutation approaches can replace the pRNA 5′/3′ ends with other sequences without affecting its correct folding and function,13,14 pRNA can be used as a carrier for ribozymes.…”
Section: Applications Of Prna In Drug Deliverymentioning
confidence: 99%
“…Ribozymes are unique RNA enzymes that can recognize and cleave other RNA molecules in a sequence‐specific fashion (34). They were initially used to inhibit gene expression in HIV virus (35) and cancer (36). Compared with the antisense oligos, ribozymes offer significant advantages: (i) they operate as site‐specific ribonucleases, resulting in catalytical cleavage of the target mRNAs; (ii); they are more stringent than antisense oligos in binding mRNA targets; (iii) controls for ribozyme activity can be made by substituting nucleotides in the catalytic core to produce an inactive ribozyme (37).…”
Section: Approaches To Studying the Function Of Endogenous Rgs Proteinsmentioning
confidence: 99%